Public Sector Digital Transformation: Analysis of Digital Literacy of Government Apparatus in Kepatihan Village, Menganti District, Gresik Regency - Iswanto, Denny; Miskan, Miskan; Elani Putri Zohandy, Devina; Siti Solikha, Wahyu (Universitas 17 Agustus 1945 Surabaya, 2024)
Digital transformation in the public sector is a strategic step to improve public service efficiency, transparency, and quality. However, the success of this transformation is highly dependent on the level of digital literacy of government officials as implementers of digital policies and programs. This study aims to analyze the digital literacy of government officials in Kepatihan Village, Menganti Subdistrict, Gresik Regency, in the context of public sector digital transformation. The research method used is descriptive qualitative with a case study approach. Data were collected through in-depth interviews, observation, and analysis of related documents. The research participants consisted of government officials from Kepatihan Village who were directly involved in implementing digital technology in public services. The results showed that the level of digital literacy of Kepatihan Village government officials varied, with most officials demonstrating a basic understanding of digital technology, but still limited in advanced technical capabilities and practical applications. Factors such as age, education, and work experience influence this level of digital literacy. In addition, the study found infrastructure constraints and technical support that still need to be improved to smooth the digital transformation process. This research provides recommendations to improve the digital literacy of government officials through continuous training and mentoring, as well as strengthening information technology infrastructure. Thus, it is expected that the digital transformation of the public sector in Kepatihan Village can run more effectively and provide maximum benefits to the community.